EMPOWERING FEMALE WRITERS FROM PESANTREN: HARNESSING THE POWER OF DIGITAL LITERACY - Fitriyah, Atiqotul; Haryanti, Novi Diah; Sabirin, Abu Bakar; Mahfudin, Irvan Aladip (Marwah: Jurnal Perempuan, Agama dan Jender, 2025)
This study explores women's empowerment through digital literacy within pesantren, focusing on three case studies: Nisaul Kamilah from Pesantren Maslakul Huda Lamongan, Mambaul Atiyah from Pesantren Sabiluth Thoyyib Pasuruan, and Munawara from Pesantren Tebuireng Jombang. Employing a qualitative approach, the research investigates how these female digital literacy advocates utilize technology to enhance students' reading, writing, and access to information. The findings indicate that digital literacy not only modernizes education in pesantren but also creates opportunities for women to work, express themselves, and contribute to da'wah. Nonetheless, challenges such as limited access to technology and concerns about its potential negative impacts remain. Support from pesantren leaders and the implementation of flexible policies are essential for empowering women and advancing education. Furthermore, women's involvement in shaping educational practices has a positive effect on the digital literacy environment, inspiring santriwati to participate in technology-based initiatives